Applying an extended theory of planned behaviour to understand influences on safe driving intentions and behaviours. (October 2022) - Armitage, Sophia; Rodwell, David; Lewis, Ioni
Highlights: Investigated influences of safe driving intentions and behaviours. Extended Theory of Planned Behaviour with Five Factor Model personality constructs applied as predictors. Intentions predicted drivers' self-reported safe driving behaviour. Personality construct, imagination, predicted intention for safe driving generally only. Significant predictors differed across the general safe driving and specific safe driving scenarios examined. Abstract: Most road safety research and interventions focus on risky or unsafe driving but understanding psychosocial motivators for safe driving behaviours may also be important in efforts to improve road safety. The current study applied an extended Theory of Planned Behaviour (TPB) including attitude, subjective norm, perceived behavioural control (PBC), together with the additional constructs of moral norm, descriptive norm, and anticipated regret in understanding drivers' intentions to engage, and self-reported engagement, in safe driving. As additional extended TPB constructs, personality constructs from the Five Factor Model of Personality (FFM; extraversion, neuroticism [emotional stability], agreeableness, conscientiousness, openness to experience [imagination]) were also investigated. Licensed drivers from Queensland, Australia, aged 17 years and older, completed an initial online survey investigating intentions for safe driving behaviours ( N = 171) followed by a second online survey-one week later investigating actual behavioural engagement ( N = 63). Participants answered items related to general safe driving and two safe driving scenarios: namely, leaving an adequate gap between vehicles on a multi-lane highway and reducing speed in storming conditions. Separate hierarchical multiple regressions were conducted to identify the motivators of intentions to engage in safe driving in each scenario. PBC and subjective norm were significant predictors of intentions to engage in general safe driving and the two specific scenarios. Attitude was a significant predictor of intentions to engage in safe driving in the specific highway scenario, moral norm was a significant predictor of intentions in both the general safe driving and the specific highway scenario, and anticipated regret was a significant predictor in the specific storming conditions scenario. Imagination was the sole significant personality-related predictor of intention and that was only in the specific highway scenario. For the predictors of self-reported performance of safe driving behaviour, these were examined regarding only the general ( N = 57), and the specific highway scenario ( N = 49) given storms/rainy weather had not occurred in the interim period between surveys. Self-reported safe driving behaviour in the general and specific highway scenario was significantly predicted by intention. This research supports the importance of understanding factors influencing safe driving behaviours and not just risky driving behaviours. Research that identifies influences on safe driving may help to inform interventions that may promote more positive, safe on-road behaviours.